Anatomical and physiological features of the growth and development of the human dentition - Skrypnyk И. Л.; Soldatova О. В. (Actual Dentistry, 2022)
Modern dentistry dictates certain rules, including the necessity to consider the etiology of the development of dentognatic anomaly and/or deformation in order to choose a proper treatment method for an orthodontic patient. Etiology is closely related to the growth and development of the human dentognathic system, which have different mechanisms at different stages and are influenced by various factors. We propose for review a sequenced and phased chronology of growth and development of the maxillofacial system in terms of age.